PEMBERDAYAAN MASYARAKAT MELALUI PENGOLAHAN LIMBAH KULIT KOPI - Wulandari, Yunita; Sinta, Ana Nur; Utami, Setyo; Muna, Izzatul (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
The primary livelihood of the residents of Sidomulyo Village is coffee farming. Although coffee production is abundant, coffee husk waste is often discarded and has not been optimally managed. Therefore, this community engagement initiative aims to empower the people of Sidomulyo Village through the utilization of coffee husk waste, which has traditionally been regarded as mere refuse. Employing a Participatory Action Research (PAR) approach, this program actively involved community members throughout the entire process—from problem identification and planning to action and reflection or evaluation. The main focus of the study is the transformation of coffee husk waste into value-added products, while simultaneously maintaining a clean environment by reducing the accumulation of waste. The findings indicate an increase in community knowledge and skills related to waste management, along with a growing awareness of the importance of environmental stewardship. Thus, not only does this initiative empowers the community in addressing local waste issues, but it also contributes to enhancing environmental awareness among residents.